To become or be made a psychoanalyst - Szecsödy, Imre (The Scandinavian psychoanalytic review, 2003)
Psychoanalysis is unique in that competence in the field can be achieved only through applying the method to oneself. Different psychoanalytic schools differ in their understanding of the unconscious, about how to approach it, or how to define the specificity of the psychoanalytic interaction. Consequently, there are differences in the criteria for the definition of the 'good-enough analysis'. There are many different opinions about how to select candidates, organise the curriculum and length of training. To define psychoanalytic talent is difficult; the uncertainty in the definition of criteria to use for selection is great; the problematic overlap between personal analysis and training is constantly present; to achieve conditions in which learning and creativity can develop is complicated by trainee, supervisor and their relationship to the Institute. Confrontations about training are often heated and divergent, as well as repetitive. Systematic studies about psychoanalytic education are very few. After a short discussion of the different concerns about selection, personal versus training analysis and the ambiguities of the supervisory situation, the author gives a review of three studies on how psychoanalytic education-as viewed by trainers and trainees-is conducted and experienced at the Swedish Psychoanalytic Institute. Training is felt to be well grounded in theory and tradition; nonetheless most do not have a sufficiently clear picture of training as a whole. Both candidates and trainers see the development of a psychoanalytic identity as the goal of training, where the competencies to be acquired are equated with important personality qualities. The candidates have a feeling of "being chosen"; they "wish to belong to a group who share an interest and fascination for psychoanalytic thinking and theory". All praise the warm and open atmosphere, and the mutual and continuous evaluations and the deep involvement of all. The surge to be rooted in an overreaching psychoanalytic ethic, the culture of gratitude within the Institute and the devotion to the task to train psychoanalytic clinicians for the future may preserve an idealised image of psychoanalysis and the fantasy that psychoanalysts are exceptional persons and give a mystifying colour to the psychoanalytic profession. This might also stand in the way of a more radical change in the traditions of training-according to the rather drastically changing climate in which psychoanalysts of the future will have to work.